Penerapan PjBL dalam meningkatkan proses kreatif menulis puisi - Aditya Ansor Alsunah; Didin Sahidin; Agus Hamdani; Ardi Mulyana Haryadi; Ninah Hasanah (Universitas Pendidikan Indonesia, 2026)
Some students have poor abilities to express ideas and to develop creative imagination in poetry writing activities in Indonesian Language and Literature learning. Therefore, this study aims to analyze the effect of implementing the Project-Based Learning (PjBL) model on students' creative process in poetry writing. The PjBL model was chosen because it emphasizes active, collaborative, and project-based learning, providing opportunities for students to explore ideas through authentic experiences and to be responsible for the final products of their learning, in the form of literary works. This study used a quasi-experimental one-group pretest–posttest design. The research subjects were 30 grade XII students at MA Fauzaniyyah. The research instruments included a creative process assessment sheet and a poetry assessment rubric that covered aspects of imagination, expression, and poetic diction. The results showed a significant increase in students' creative processes following the implementation of the PjBL model. This increase was seen in the ability to develop ideas, enrich imagination, and express ideas poetically. In addition, students showed higher involvement and enthusiasm during the learning process. The PjBL model can support more meaningful, context-based poetry-writing learning.